2007
DOI: 10.1021/ja0763504
|View full text |Cite
|
Sign up to set email alerts
|

Reversible N−N Coupling of NO Ligands on Dinuclear Ruthenium Complexes and Subsequent N2O Evolution:  Relevance to Nitric Oxide Reductase

Abstract: Contents Experimental ProceduresTable S1.Crystallographic data for 2b•0.5(CH 2 ClCH 2 Cl) and 2c•C 6 H 5 Me

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 18 publications
7
88
0
Order By: Relevance
“…96 DFT calculations (B3LYP level of theory using a LANL2DZ basis set for Ru) revealed that the highest occupied molecular orbital (HOMO) in this complex is primarily localized on the 18 N-N bond. 95 Significantly, the hyponitrite ligand in this complex is essentially identical to the (NO) 2 dimers proposed to form on metal surfaces during catalytic NO reduction. 22 Scheme 10.…”
Section: Scheme 2 Synthesis Of Trans-hyponitrous Acidmentioning
confidence: 60%
“…96 DFT calculations (B3LYP level of theory using a LANL2DZ basis set for Ru) revealed that the highest occupied molecular orbital (HOMO) in this complex is primarily localized on the 18 N-N bond. 95 Significantly, the hyponitrite ligand in this complex is essentially identical to the (NO) 2 dimers proposed to form on metal surfaces during catalytic NO reduction. 22 Scheme 10.…”
Section: Scheme 2 Synthesis Of Trans-hyponitrous Acidmentioning
confidence: 60%
“…Ruthenium complexes bearing bis(pyrazolyl)borate (Bp) and tris(pyrazolyl)borate (Tp) ligands have attracted considerable research attentions [24][25][26][27]. However, only a limited number of ruthenium nitrosyl complexes with polypyrazolyborate ligands have been reported [28][29][30][31][32][33][34][35]. Onishi et al have reported the preparation and novel reactivities of the ruthenium nitrosyls bearing Tp ligand and their alkynyl derivatives [28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…However, only a limited number of ruthenium nitrosyl complexes with polypyrazolyborate ligands have been reported [28][29][30][31][32][33][34][35]. Onishi et al have reported the preparation and novel reactivities of the ruthenium nitrosyls bearing Tp ligand and their alkynyl derivatives [28][29][30][31][32][33][34][35]. Polypyrazolylmethanes, such as bis(3,5-dimethyl-1-pyrazolylmethane) (Bpm * ) and tris(1-pyrazolyl)methane (Tpm), are the neutral analogues of the Bp and Tp ligands [36,37], which are isosteric and isoelectronic with the anionic polypyrazolyborates.…”
Section: Introductionmentioning
confidence: 99%
“…These results are fully consistent with experimental observations. 44,45 3.3. Proton-Assisted Mechanisms.…”
Section: Geometric and Electronic Structures Of Dinitrosylmentioning
confidence: 99%
“…Very recently, we have shown that protons can play a significant role in the decomposition of NO (2NO → N 2 + O 2 ) catalyzed by a copper ion-exchanged zeolite Cu-ZSM-5, where N 2 O is one of the important intermediates in the catalytic cycle. 43 Arikawa and co-workers 44,45 recently synthesized a dinuclear ruthenium complex [(TpRu) 2 …”
Section: ■ Introductionmentioning
confidence: 99%